Ethical Challenges in Multidisciplinary Approach to Service-Learning - Calumpang, Pemenorejoan M.; Clarida, Sergio; Tantoy, Laura A. (Silliman Journal, 2022)
Service Learning (SL) responds to one of the domains in the National Competency-Based Teacher Standards which is to establish learning environments that respond to the aspiration of the community. Thus, in Pilgrim Christian College, SL was integrated with NSTP, Practice Teaching, and Entrepreneurship / Franchising Classes. Different communities were identified as partners in SL. These communities were groups of people with common characteristics such as parents of children at a Day Care Center and the survivors of Sendong. Memoranda of Agreement were formulated to protect both parties–the program implementors and the partner communities. Positive outcomes were objectively observed but limited to written and verbal testimonies among the students, members of the partner communities, and the faculty. Practical application of concepts from the classroom to the field was highly appreciated. In the implementation of SL, PCC tried to address the domain of the learning environment. Being fair and making sure that the physical environment was safe and conducive to learning were among the ethical and human protection issues considered for dissection. A formal construct focused on consent, confidentiality, competence, and conflict of interest. Since PCC is a UCCP and bible-based institution, and the students’ parents or families come from different religious orientations, a written consent/ informed decision from the parents has become a challenge, especially in getting their consent for the inculcation of biblical values among the students, as an add-on in the literacy program. With implementors overwhelmed with the program, confidentiality should have been emphasized especially among the students and community partners. In terms of competence, selection of cooperators, entry issues, and sustainability were the essence. For the partner communities, conflict of interest may have taken place especially when required to attend the worship services of the Pilgrim Christian Community Fellowship (PCCF); however, the judgment may have been ethical itself with regard to culture and situations. Sustainability in implementing SL, while considering ethical and human protection issues, is PCC’s goal. Respecting people as ends, not means, being listened to, is ensured.